Towards pluriversal community informatics: Connecting Indigenous communities in Borneo and Canada across time and space - McMahon, Rob; Zaman, Tariq (University of Waterloo Library, 2024)
In this article we reflect on pluriversal connections for Community Informatics (CI), drawing from our collective experiences working with Indigenous Peoples in Borneo and Canada. Building on Michael Gurstein’s foundational work and situating it in relation to contemporary debates around digital equity and inclusion, we present summaries of collaborative, iterative, locally-grounded participatory action research projects that illustrate the enduring methodological, ethical and conceptual questions raised in CI. Through our interactions and shared experiences, these examples also demonstrate Gurstein’s (2012) focus on connecting across geographic and cultural boundaries in ways that respect the self-determined nature of place-based communities.